Hubungan Kelompok Maseral Liptinit dan Vitrinit dengan Tipe Kerogen Batuan Sumber Hidrokarbon pada Serpih Formasi Kelesa Bagian Atas, Kuburan Panjang, Riau - Zajuli, Moh. Heri Hermiyanto; Panggabean, Hermes; Hendarmawan, Hendarmawan; Syafri, Ildrem (Pusat Survei Geologi, 2017)
This study focuses on correlation of liptinite and vitrinite maceral to kerogen type of shale from Kelesa Formation in Kuburan Panjang areas, Sumai sub-basin, Central Sumatra Basin. The composition of the organic material consists of vitrinite maceral ranged from 0.2 to 5%, liptinite from 0.6 to 4.7%, the type of minerals in the form of pyrite from 0.2 to 16%, and 0.2 -24.2% of carbonate, as well as clay minerals are the most dominant component ranged between 71.6 -98%. TOC values of the shale range from 1.18% to 7.17%, which indicate ability of the shale as a good source rock. Kerogen type analysis of theshale in the research area tends to indicate I, II and III kerogen types. There is an influence of the liptinite and vitrinite maceral groups abundance to the type of kerogen, where liptinit maceral group tends to produce type I and II kerogen. Key word : Kelesa Formation, Eocene-Oligocene, Central Sumatera Basin, Vitrinite, Liptinite